Multi-objective forest restoration planning in Costa Rica : Balancing landscape connectivity and ecosystem service provisioning with sustainable development - Martinez Salinas, Alejandra; y otros 2 autores más (Elseiver, 2022)
It uses a spatial planning tool (Marxan) to identify priority areas for restoration meeting multiple objectives throughout a biological corridor in Costa Rica. A restoration plan is presented which seeks to maximize the provision of services related to the forest while minimizing the impact on current land uses. It quantifies tourism and seed dispersal services using species distribution models. It uses the InVEST carbon sequestration model to quantify carbon storage potential. It shows how a landscape-scale forest restoration plan that takes into account only forest and ecosystem connectivity service delivery capacity may differ greatly from a plan that considers potential impacts on local livelihoods. Notes the need to pay attention to the use of adequate opportunity cost estimates, to avoid potential conflicts between restoration objectives and other legitimate land uses.